2023
DOI: 10.21203/rs.3.rs-2507673/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of pathologic complete response after single-dose MR-guided partial breast irradiation in low-risk breast cancer patients: the ABLATIVE-2 trial - a study protocol

Abstract: BACKGROUND: Partial breast irradiation (PBI) is standard of care in low-risk breast cancer patients after breast-conserving surgery (BCS). Pre-operative PBI can result in tumor downstaging and more precise target definition possibly resulting in less treatment-related toxicity. This study aims to assess the pathologic complete response (pCR) rate one year after MR-guided single-dose pre-operative PBI in low-risk breast cancer patients. METHODS: The ABLATIVE-2 trial is a multicenter prospective single-arm trial… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Given the exploratory nature of this study, our decision to use this dose was based on prior studies [5,28,29,30] that have demonstrated its effectiveness without signi cant radiotherapy related side effects and improved overall quality of life. Given the variability among studies investigating singlefraction accelerated partial breast irradiation [4,5,6,28,29,30], particularly in terms of the time intervals and techniques used, it is anticipated that a portion of patients will demonstrate a response to treatment. Nevertheless, since no study to date has explored the response to treatment 6 weeks after single-fraction preoperative radiation therapy using the MR linac, these outcomes remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the exploratory nature of this study, our decision to use this dose was based on prior studies [5,28,29,30] that have demonstrated its effectiveness without signi cant radiotherapy related side effects and improved overall quality of life. Given the variability among studies investigating singlefraction accelerated partial breast irradiation [4,5,6,28,29,30], particularly in terms of the time intervals and techniques used, it is anticipated that a portion of patients will demonstrate a response to treatment. Nevertheless, since no study to date has explored the response to treatment 6 weeks after single-fraction preoperative radiation therapy using the MR linac, these outcomes remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is expected to continue, driven by the increasing prevalence of risk factors, population growth, and aging [1,2]. Despite this, mortality from early-stage breast cancer has signi cantly decreased, with the global 5-year net survival rate estimated to increase from 67.9-78.2% [3,4]. Simultaneously, there is a shift towards personalized and less invasive therapies, aimed at deescalating therapy, improving cosmetic outcomes, and reducing radiation therapy-related toxicity, all while ensuring the safety and e cacy of oncological care [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations